Effect of bladder distension on arginine vasopressin secretion in rats - Yosuke Morizawa; Kazumasa Torimoto; Shunta Hori; Daisuke Gotoh; Yasushi Nakai; Makito Miyake; Kiyohide Fujimoto (BMC Research Notes, 2019)
Abstract Objective Urine production is regulated throughout the night to ensure that it remains within functional bladder capacity. Increasing bladder capacity may thus play an important role in urine production. We investigated arginine vasopressin (AVP) secretion in female rats anesthetized with urethane in the daytime and nighttime under distended/empty bladder conditions. Chronological serum AVP was measured by enzyme immunoassay in rats with distended or empty bladders. Results The mean baseline AVP level was significantly higher in the nighttime than in the daytime (17.21 ± 5.29 vs 11.68 ± 3.16 pg/mL, p = 0.0019). However, serum AVP levels did not change with time in the daytime or nighttime, regardless of an empty or distended bladder. We therefore concluded that AVP secretion was unaffected by bladder filling.